RNAi-mediated silencing of the Bmi-1 gene causes growth inhibition and enhances doxorubicin-induced apoptosis in MCF-7 cells - Wu,Xiang-mei (2009)
The oncogene Bmi-1 is a member of the Polycomb group gene family. Its expression is found to be greatly increased in a number of malignant tumors including breast cancer. This could suggest Bmi-1 as a potent therapeutic target. In this study, RNAi was introduced to down-regulate the expression of Bmi-1 in a highly malignant breast adenocarcinoma cell line, MCF-7. A thorough study of the biological behavior and chemosensitivity changes of the MCF-7 cells was carried out in context to the therapeutic potential of Bmi-1. The results obtained indicated that siRNA targeting of Bmi-1 could lead to an efficient and specific inhibition of endogenous Bmi-1 activity. The mRNA and protein expression of Bmi-1 were determined by RT-PCR and Western blot, respectively. Furthermore, silencing of Bmi-1 resulted in a drastic inhibition of the growth of MCF-7 cells as well as G1/S phase transition. The number of target cells was found to increase in phase G0/G1 and decrease in the S phase, but no increase in the basal level of apoptosis was noticed. On the other hand, a reduction in the expression of cyclin D1 and an increase in the expression of p21 were also noticed. Silencing of Bmi-1 made the MCF-7 cells more sensitive to the chemotherapeutic agent doxorubicin and induced a significantly higher percentage of apoptotic cells. Here, we report on a study regarding the RNAi-mediated silencing of the Bmi-1 gene in breast cancer.